To Determine the Frequency of Modes of Delivery in Short-Statured Primigaravidae at Term (Medical Forum Monthly, 2024)
Objective: The aim of this study was to determine the frequency of modes of delivery in short-statured primigaravidae at term.Study Design: Descriptive cross sectional study.Place and Duration of Study: This study was conducted in the Department of Obstetrics and Gynaecology, Khyber Teaching Hospital, Peshawar, from Apr 2010 to Mar 2011.Materials and Methods: 369 primigravidae,15-35 years old with singleton pregnancy, cephalic presentation and with height less than 152 cm were randomized for the study. Pelvic assessment was done clinically in all and radiologically in some cases. Monitoring of labour was done and modes of deliveries were recorded.Results: Mean age and height was 25.57years + 3.22SD and 148.9cm + 2.1SD respectively. Normal vaginal delivery occured in 96(26.02%) while 32(8.67%) patients had instrumental vaginal delivery (13 (3.52%) vacuum and 19 (5.15%) outlet forceps). Elective and emergency cesarean section was done in 28 (7.59%) and 207 (56.09%) patients respectively.Conclusion: Primigravidae with short stature constitutes a high risk group for poor progress in labour. Emergency cesarean section is more common in short statured primigravidae.